E-Word of Mouth and its Influence on Adolescent Purchase Behavior Toward Dietary Supplements - Alam, Dr. Mohammad Zulfeequar (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of the study was to examine the perceived trustworthiness of the electronic word of mouth (eWOM) on attitude and their purchase intention toward dietary supplements, particularly with Saudi female adolescents. Materials and Methods: The sample of 1027 adolescent Saudi females was contacted online. Excel and Social Science Statistics were used to analyze the data as per the requirement of the study. The hypothesis that has been built in this study was tested with Chi-squire test at significance level of P ≤ 0.05, and result was analyzed and interpreted accordingly. Results and Discussion: More than 50% believed that dietary supplements have a nice and favorable effect on health. The study’s findings suggest that the perceived trustworthiness of eWOM has a significant impact on attitude toward dietary supplements and impacts the purchase intention of adolescents. Conclusion: There is a positive relationship between the trustworthiness of eWOM on purchase intention of dietary supplements among the respondents. Overall, it is recommended that the marketer of this product (dietary supplements) should maintain the user’s perception and build brand image using the proper positioning of the marketing mix that suits the target consumers.